CARACTERÍSTICAS Y FACTORES DE RIESGO DE LA INFECCIÓN DE VÍAS URINARIAS CON CULTIVO POSITIVO PARA BETALACTAMASAS DE ESPECTRO EXTENDIDO EN ADULTOS ATENDIDOS EN URGENCIAS EN EL HOSPITAL MILITAR CENTRAL - Luis Eduardo Silva Diaz-Granados (Asociación Colombiana de Infectología, 2018)
Objectives: The objective of the study was to describe the risk factors of adult patients with urinary tract infection (UTI) with extended spectrum beta-lactamaseproducing bacteria (ESBL) in the population of the Hospital Militar Central (HMC) in 2012 and 2014. Risk factors such as previous hospitalization, chronic care unit resident, previous use of antibiotics, previous use of steroids, urinary tract instrumentation and bladder catheter were analyzed. Material and methods: We conducted a retrospective case-control study, the source of information were the medical records of adult patients older than 18 years of age, who consulted the emergency department of the HMC, diagnosed with UTI by a bacterium carrying ESBL. The characteristics of the sample were established and the risk factors associated with the development of infection by ESBL-producing bacteria in the selected sample were determined. Results: Of the 1986 isolates that fulfilled the selection criteria, 14% reported microorganisms producing ESBL. Of the six risk factors studied, three presented a statistically significant difference: previous hospitalization, previous use of antibiotics and urinary tract instrumentation. Of the risk factors identified, a multivariate analysis was performed in which the previous use of antibiotics and urinary tract instrumentation were maintained as significant risk factors that increase the risk of UTI by ESBL-producing bacterias in 1,9 and 3,18 times respectively. Conclusions: Although the other risk factors described did not reach a statistically significant difference, prospective studies should be performed to assess their association with the development of resistant germ infections and to develop a risk scale that allows emergency personnel to administer targeted antibiotic therapy to this population subgroup.